An Analysis of Theme on Selected Taylor Swift's Song Lyrics - Rahayu, Retno, Dra. Malikatul Laila, M.Hum (2017)
Theme and Rheme are important components in meaning-organizing. Not only on standard written texts but it also applies in written art or literature work which is usually artistically constructed. Song lyric, for example, also has meaning realized. Theme constitutes the main part of clause, because comprehending the Theme may help to understand the whole clause. Therefore, this research identifies the types of Theme and finds out the textual meaning realized on selected Taylor Swift's song lyrics. The objectives of this study are: (1) to identify the types of Theme in the Taylor Swift song lyrics, and, (2) to explain the textual meaning realized in Taylor Swift's songs. This research is analyzed by using descriptive qualitative method. The data are all clauses taken from 10 Taylor Swift's song lyrics, entitled Love Story, You Belong with Me, Enchanted, You're Not Sorry, Speak Now, Haunted, Blank Space, Forever Always, Fearless and 22. Data are analyzed by using Gerot and Wignell (1994) theory which includes the type of Theme, then the writer describes the textual meaning realized in the song. The result of the study shows that 4 types of Theme are applied by the author in her song. There are Unmarked and Marked Topical Theme, Textual and Interpersonal Theme. Among the 4 types of Theme used, Unmarked Topical Theme is most frequently used by the author in writing her songs lyrics; that is 59, 6 %, the next position is Textual Theme 24,8 %, Marked Topical Theme 8, 5%, and the last one is Interpersonal Themes 7, 2 %. After identifying the types of Theme, the writer describes the meaning realized in the song based on the Theme type applied. The pedagogical implication of this research is to make the students master the grammar easier and write a text coherently.